Pengaruh Keyakinan Diri dan Dukungan Keluarga terhadap Pengambilan Keputusan Karier SMA Sederajat - Didit Darmawan; Abdullah Hilmi; Muhammad Bustanul Arifin (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Teenage students in secondary school face a critical period in making career decisions, but many of them experience confusion and anxiety during this phase. This study aims to explore how self-efficacy and family support influence career decision-making among high school students or their equivalents. Qualitative research methods were used through a literature review, collecting data from various sources including journals, scientific studies, and related books. The results of the study show that self-efficacy significantly increases students' maturity and clarity in choosing their career paths. In addition, family support, both emotional and practical, plays an important role in increasing students' confidence and determination in choosing a career. The interaction between internal elements (self-efficacy) and external factors (family support) greatly influences the career decision-making process. This study highlights the importance of collaboration between schools and families in providing career guidance, social skills development, and effective communication so that students can make appropriate and realistic career decisions in line with their abilities and the demands of the job market. Students' willingness is shaped by internal influences such as self-efficacy and external influences such as family support. This study is important for understanding the role of these two factors in the career decision-making of high school students.